The State that Works. On Finnish Public Policies - Woźniak, Wojciech (Lodz University Press, 2022)
The book „The State that Works. On Finnish Public Policies” summarizes few years of author’s research into various aspects of functioning of the Finnish state, depicting them in a broad, historical and cultural perspective. The aim of the books is the description and analysis of mainly internal factors relating to the political processes and public policy-planning that allowed Finland unprecedented development and promotion to the group of most economically and technologically advanced states in the world. It was possible to achieve even though in the mid-21 century Finland still remained a peripheral country with the economy based on a basic production and export of the wood, it’s only natural resource available on a mass scale. In the introduction, author describes crucial geographical, historical and cultural factors determining he institutions’ building processes and the situation of Finnish society before gaining the independence in a year 1917 and in the first decades of sovereign Finnish state. In the following parts, devoted to economic, educational and social policies, he describes political processes and concrete solutions implemented in these spheres which at the turn of the XX and XXI century allowed achieving aforementioned success and increase in the affluence and quality of life of Finnish people. In the concluding chapter, author pays special attention to the role of education, knowledge and science in planning and designing or public policies in Finland as a key factors allowing the radical transformation of Finnish economy and society. The books ends with a discussion about the major challenges that Finnish state and society confront at the moment and most promising future research fields.